La Inteligencia Artificial (IA): ¿Un desafío para la espiritualidad? - Cevallos, Eliana (Revista de espiritualidad, 2023)
Artificial intelligence (AI) is a growing reality with varied applications that poses many challenges, particularly to the notion of personhood and, consequently, to the understanding and experience of spirituality. This article takes stock of this situation by reflecting on the meaning of intelligence. It then reviews the applications of AI in contemporary life. The article concludes with a more speculative view on the possible implications of AI for spirituality, underlining that, although the outlook appears daunting, AI can provide new perspectives and serve as an avenue for a strengthening of spirituality.